2020
DOI: 10.3390/polym12122962
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Response Optimization of Tensile Creep Behavior of PLA 3D Printed Parts Using Categorical Response Surface Methodology

Abstract: Three-dimensional printed plastic products developed through fused deposition modeling (FDM) endure long-term loading in most of the applications. The tensile creep behavior of such products is one of the imperative benchmarks to ensure dimensional stability under cyclic and dynamic loads. This research dealt with the optimization of the tensile creep behavior of 3D printed parts produced through fused deposition modeling (FDM) using polylactic acid (PLA) material. The geometry of creep test specimens follows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 48 publications
(53 reference statements)
1
15
0
Order By: Relevance
“…It is rare in the literature for the creep performance of 3D-printed FRP materials to be investigated. Waseem et al [ 70 ] performed a study where creep performance of 3D printed PLA was investigated using multiple response optimization. The study utilized different performance parameters such as infill pattern, layer height and infill percentages.…”
Section: Mechanical Properties Of Fiber-reinforced Polymer Compositesmentioning
confidence: 99%
“…It is rare in the literature for the creep performance of 3D-printed FRP materials to be investigated. Waseem et al [ 70 ] performed a study where creep performance of 3D printed PLA was investigated using multiple response optimization. The study utilized different performance parameters such as infill pattern, layer height and infill percentages.…”
Section: Mechanical Properties Of Fiber-reinforced Polymer Compositesmentioning
confidence: 99%
“…Instead of linear regression, the response surface method (RSM) uncovers the interconnectivity between various controllable factors and several response variables using nonlinear modeling. It should be acknowledged that RSM serves as an approximation method that provides a relatively easy method for modeling, estimating, and optimizing based on target parameters [ 52 , 53 , 54 ]. By use of mathematical and statistical techniques, an empirical model is created from experimental data and is used to evaluate the fit to a statistical model (linear, quadratic, cubic or two-factor Interaction), as described in Equation (4) below.…”
Section: Methodsmentioning
confidence: 99%
“…Same as above, the independent variables A, B, and C represent sulfur content, paraffin oil content, and void content, respectively. The coefficients ( ) determined by the model within the linear and quadratic sections dictate the influence each respective variable has on the output, Y, while the Two-Factor coefficients ( ) of the quadratic model above quantify the level of influence that interactions between two variables have on the output [ 52 , 53 , 54 , 55 ]. As mentioned above, formulating is a balance between various additives and RSM allows for the user to determine, to some degree, the interaction effects between two controllable variables.…”
Section: Methodsmentioning
confidence: 99%
“…PLA, a partially crystalline polymer, is biodegradable (compostable) and has low melting temperature but has limited thermal stability [14]. The performance of these two materials for 3D printing has been assessed [15][16][17][18], particularly in terms of dimensional accuracy [19,20], surface roughness [21], mechanical performance [22] and emission of volatile organic compounds (VOC) [23,24]. For the 3D printing of a compact omnidirectional wheel, Rubies and PalacĂ­n [25] observed that when using 100% infill density, PLA yielded a better mechanical performance than ABS.…”
Section: Related Workmentioning
confidence: 99%